al-‘lāqah baina mamlikatay Mārī wa-Yamḥād (Ḥalab) fī ’l-’alf al-ṯānī qabla ’l-mīlād - Ša’ṯ, Šauqī
ersch. 1986?; The Relationship between the Kingdoms of Mari and Yamhad (Aleppo) in the Second Millennium B.C.